Guía metodológica para la integración del sistema de gestión, ISO 14001: 2004, OHSAS 18001:2007 para empresas de explotación y producción de agregados pétreos (2015)
The present work describes a way to integrate the management of hazards and aspects generated in the Exploitation and Production of Stone Aggregates whose approach is the approach of measures and useful actions of mitigation and control of the problems of security, health and risks that they face commonly workers in this sector, and at the same time consider those relevant to the environmental impact of this activity. For which the present thesis will show a methodological guide to integrate an Occupational Health and Safety Management System based on the OHSAS 18001: 2007 standard and an ISO 14001: 2004 Environmental Management System, where step by step is illustrated how to perform the identification of threats, which in this case are dangers and aspects, evaluation of consequences or risks and impacts and establishment of controls. Additionally, the characterization of the process is presented as a model and starting point in an HSE System and the identification of legal requirements.